Digitization of indigenous knowledge on forest foods and medicines. (June 2017) - Sraku-Lartey, Margaret; Acquah, Stella Britwum; Samar, Sparkler Brefo; Djagbletey, Gloria Djaney
This paper discusses the digitization of indigenous knowledge on forest foods and medicine for the effective management of Ghana's forest resources. The paper is based on a survey conducted in nine communities in Ghana where primary data were obtained from 606 respondents using in-depth face-to-face interviews. The aim of the study was to assess what knowledge local communities had about products of the forest especially indigenous forest foods and medicine. The findings reveal that local communities have an in-depth knowledge of indigenous forest foods and medicines. They are conversant with what foods and medicines are available in the forests, how they are consumed and when they mature. The study reveals that consumption of indigenous forest foods is on the decline, while the use of traditional medicine is on the ascendancy. The study recommends the promulgation of laws and legal instruments to protect communities from bio-piracy.